Involving IDPs in the Darfur peace process - David Lanz (Forced Migration Review, 2008)
The UN estimates that there are 2.4 millionIDPs in Darfur –over one third of the totalpopulation. There can be no meaningfulpeace process without their involvement.Giving IDPs a formal seat in official peacenegotiations is problematic but there areother ways to ensure their participation.